HUBUNGAN ANTARA POSTUR KERJA DENGAN TINGKAT KELUHAN SUBYEKTIF MUSKULOSKELETAL PADA PENJAGA PINTU TOL TEMBALANG SEMARANG - Dhandy Dwi Yustica; Suroto Suroto; Ekawati Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Muculoskeletal disorders are complaints on parts of the skeletal muscles that felt by someone start by minor disorders up to very sick. One of disease that affects many workers was musculoskeletal disorders, musculoskeletal disorders therefore an important concern for all circles. The purpose of this study was to determine the correlation between work posture with the level of subjective musculoskeletal disorders in toll road keeper Tembalang Semarang. Type of this study is explanatory research using cross sectional approach. The number of samples in this study is the total of population is 30 people. Data analysis using Spearmen Rank correlation test, with significance level of 95%. The result of this study showed the majority of respondent felt the musculoskeletal disorders lightweight category are 46,7%. The statistical analysis result showed there is correlation between work posture (p=0,002), wrist posture (p=0,037), twisting wrist posture (p=0,011), and neck posture (p=0,009) with the level of subjective musculoskeletal disorders in toll road keeper Tembalang Semarang. There is no correlation between upper arm posture (p=0,723), forearm posture (p=0,903), back posture (p=0,767) dan leg posture (p=0,155) with the level of subjective musculoskeletal disorders in toll road keeper Tembalang Semarang. From this study we can conclude that 70% of workers toll road keeper Tembalang Semarang had musculoskeletal disorders caused by occupational factors and individual characteristics. The suggestion for company to provide education about appropiate work postures and healthy lifestyle, so that all workers can avoid musculoskeletal disorders and minimize the risk of disease to be handle in the future.